Rekonstruksi Pendidikan Hukum Islam sebagai Fondasi Etika di Era Masyarakat 5.0 - Ari Arkanudin; Miftahur Rohman (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2026)
The rapid transition toward Society 5.0 has introduced a complex landscape where advanced technology and human values intersect, often leading to ethical ambiguity in digital interactions. This study addresses the urgent need to reposition Islamic Legal Education not merely as a set of ritualistic rules but as a robust ethical foundation to navigate these contemporary challenges. The primary objective of this research is to reconstruct the framework of Islamic Legal Education by integrating the principles of Maqashid al-Shari’ah with modern digital ethics to ensure its relevance in a technology-driven civilization. This qualitative study employs a library research method with a philosophical-normative approach, analyzing various academic literacies concerning Islamic law and the characteristics of Society 5.0. The scope of the discussion covers the transformation of curriculum, pedagogical shifts, and the internalisation of prophetic values in digital spaces. The findings suggest that a reconstruction is essential through a paradigm shift from textual-formalistic learning to a more contextual-ethical approach. The study concludes that by emphasizing the protection of human dignity (hifz al-nafs) and intellect (hifz al-‘aql) within the curriculum, Islamic Legal Education can serve as a primary ethical filter against digital threats such as disinformation, cyber-crime, and dehumanization. This integration ensures that the advancement of Society 5.0 remains aligned with humanitarian values and spiritual integrity.